Enhanced gaze‐following behavior in Deaf infants of Deaf parents. Issue 2 (15th October 2019) - Brooks, Rechele; Singleton, Jenny L.; Meltzoff, Andrew N.
Abstract: Gaze following plays a role in parent–infant communication and is a key mechanism by which infants acquire information about the world from social input. Gaze following in Deaf infants has been understudied. Twelve Deaf infants of Deaf parents (DoD) who had native exposure to American Sign Language (ASL) were gender‐matched and age‐matched (±7 days) to 60 spoken‐language hearing control infants. Results showed that the DoD infants had significantly higher gaze‐following scores than the hearing infants. We hypothesize that in the absence of auditory input, and with support from ASL‐fluent Deaf parents, infants become attuned to visual‐communicative signals from other people, which engenders increased gaze following. These findings underscore the need to revise the 'deficit model' of deafness. Deaf infants immersed in natural sign language from birth are better at understanding the signals and identifying the referential meaning of adults' gaze behavior compared to hearing infants not exposed to sign language. Broader implications for theories of social‐cognitive development are discussed. A video abstract of this article can be viewed at https://youtu.be/QXCDK_CUmAI Abstract : This study is the first experimentally controlled test of gaze following with Deaf infants of Deaf parents (DoD). We found that DoD infants had significantly enhanced gaze following compared to hearing infants of hearing parents (HoH). We hypothesize that Deaf infants immersed in natural sign language from birth become attuned to visual‐communicative bodily signals from other people, which engenders accelerated gaze following. The results reveal striking malleability in gaze following based on input.